Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1177/1066896906290560
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Rhabdomyosarcoma of the Paranasal Sinuses in a 57-Year-Old Woman With 1:16 Translocation

Abstract: Alveolar rhabdomyosarcoma is an uncommon tumor. It is a rare malignancy in adults and rarely occurs in paranasal sinuses in those aged older than 50 years. This report describes a locally invasive and destructive alveolar rhabdomyosarcoma arising in the ethmoid sinus of a 57-year-old woman. The small round blue cell tumors are positive for myogenin by immunohistochemistry and have a karyotype of 45, XX, -5, -13, der(16)t(1;1) (q21;q13) by cytogenetic analysis. Fluorescence in situ hybridization demonstrated a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In pediatric alveolar RMS, for example, translocations involving FKHR are the hallmark of this subtype, with most patients having t(2;13)(q35;q14) or t(1;13)(p36; q14) translocations. 26 Abnormalities of FKHR with or without the typical translocations were identified in adults [27][28][29] but the frequencies of these abnormalities in adults are unknown. Significantly, in our study, alveolar histology was not found to be associated with worse survival than the embryonal subtype when tested using a multivariate model in adults.…”
Section: Discussionmentioning
confidence: 99%
“…In pediatric alveolar RMS, for example, translocations involving FKHR are the hallmark of this subtype, with most patients having t(2;13)(q35;q14) or t(1;13)(p36; q14) translocations. 26 Abnormalities of FKHR with or without the typical translocations were identified in adults [27][28][29] but the frequencies of these abnormalities in adults are unknown. Significantly, in our study, alveolar histology was not found to be associated with worse survival than the embryonal subtype when tested using a multivariate model in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Most cases of adult sinonasal RMS have been reported in patients less than 35 years of age with a few scattered reports in older patients. [11][12][13]21 In the current study, however, more than 50% of the patients were >35 years old at the time of diagnosis, and overall, 23% of patients were greater than 50 years old. In fact, 1 patient was 86 years old at the time of diagnosis, so whereas RMS is extremely rare in the elderly, the diagnosis should never be excluded without thorough evaluation.…”
Section: Discussionmentioning
confidence: 79%
“…4 Parameningeal RMSs have been rarely reported in adults, particularly young adults. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] We report 13 adult patients, ranging in age from 18 to 86 years, with RMS involving parameningeal sites, predominantly the sinonasal cavity.…”
Section: Embryonal and Alveolar Rhabdomyosarcoma Of Parameningeal Sites In Adults: A Report Of 13 Casesmentioning
confidence: 99%
“…McManus et al 27 reported that up to 11% of ARMSs possessed der(16)t(1;16)(q21;q13). Manucha et al 28 also reported a case of ARMS arising in the ethmoid sinus, which presents 45, XX, −5, −13, der(16)t(1;1)(q21;q13).…”
Section: Discussionmentioning
confidence: 97%